Pengaruh kompensasi, disiplin kerja dan motivasi kerja terhadap kinerja karyawan - Indah Silvia Sari; Lilis Lisnawati; Mellysa Padma Paramita (Jurnal Integrasi Sumber Daya Manusia, 2023)
The success achieved by Bank BCA cannot be separated from the important role of HR. Therefore, the Bank is committed to developing a highly competent workforce that has the agility, mindset to continue to grow, and adheres to BCA's values to run the business amidst dynamic industrial developments. The concept of Branch Service Quality (BSQ) is used by Bank BCA to assess employee performance based on respondents' perceptions which is done independently. This is done by the bank as an effort to maintain the quality of service which is currently good, where this is done by evaluating employee performance based on customer perceptions. The number of respondents in this study were 42 employees of Bank BCA KCU Kedoya Permai. This research is quantitative by using analytical methods with the SPSS program. The results of this study are that there is an influence between compensation, work discipline and work motivation on employee performance partially and simultaneously.